Determining factors of productivity in Mexican public universities (Revista LIDER, 2020)
Given the scarcity of resources, public universities have placed a special interest in achieving their objectives efficiently, the above becomes more relevant because the university is an organization with non-financial goals, but it requires public resources to operate. The objective of this study is to estimate the productivity of the mexican public universities during the period 2007 to 2017, and for this, the nonparametric technique of the Data Envelopment Analysis was used to estimate the Malmquist Productivity Indexes to a total of 44 public universities. The main findings show that there is a positive evolution in productivity which, on average, represents 5,2% and that this has a more significant relationship with the improvement of research procedures, and not necessarily with the efficient use of resources of the units analyzed. The main conclusions are that, based on the Malmquist Productivity Indexes, it is possible to know which factors contribute mainly to productivity, however, the financing schemes for the Mexican University context could influence the performance of the managers and in their results.